A review for analyzing critical factors affecting indoor robot operation: Evidence-based design approaches - Jeong, Hojeong; Seo, Seungha; Kim, Sungjin (Edelweiss Applied Science and Technology, 2025)
This study addresses the growing need for architectural environments that support stable navigation and perception performance of service robots as their deployment expands. Based on the principles of Evidence-Based Design (EBD), the research investigates correlations between robotic performance and the physical properties of architectural finishing materials. While conventional EBD has focused on human responses, evidence concerning environmental factors that influence robotic sensors and locomotion remains limited. This study examines service robot performance indicators, perception accuracy, path stability, and collision rate and relates them to material properties such as reflectance, coefficient of friction, surface roughness, illuminance uniformity, and transparency. The findings indicate that reflectance and lighting uniformity are critical determinants of sensor recognition, while friction and surface roughness strongly affect navigation stability. In addition, transparent obstacles and lighting conditions act as moderating factors that impact both perception and mobility. As a foundational investigation, this study provides baseline evidence for a correlation-based evaluation framework that can inform future design, construction, and operational guidelines for robot-friendly built environments.